Influencia de la familia en el bienestar integral de los adultos mayores que asisten al centro CAAM del IESS- Loja en la actualidad - Ojeda Gualán, Carlos Andrés (2025)
The impact of the family on the integral well-being of the retired older adult in the CAAM (Care Centre for the Elderly) of IESS Loja focuses on the role of family support in the physical, emotional, cognitive and social needs of the elderly population in the developing world, especially in Ecuador, where the ageing population has grown enormously. The quality of family support affects aspects of well-being that integrate this population group physically, emotionally, socially and economically. The family plays a special role in the care and support of the elderly, although support is sometimes limited by issues related to the financial situation, health complications or the geographical nature of societies. The aim of this research is to understand the purpose of family support with particular reference to the emotional state of retired older adults. From a social work perspective, it highlights the role of professional intervention in consolidating family relationships, fostering interrelationships and defending the rights of older people, strengthening citizenship and facing the challenges of ageing in society. The study concludes that family support has an important impact on the emotional, physical and social state of older people. Thus, those with positive family relationships appear to have better ratings of their self-esteem, life satisfaction and health status